Identification of Leading Agricultural Commodities in Simalungun Regency (2019–2023): A Location Quotient Analysis - Muhammad Yusuf Harahap; Mutia Annisa; Agnes Monica Sianipar; Nakita; Enjel Widia Sari Gea; Respa Mellia Sirait; Albi Sutandi (Perpustakaan dan Penerbitan Unismuh Makassar, 2025)
This study aims to identify leading agricultural commodities in Simalungun Regency during the 2019–2023 period using the Location Quotient (LQ) approach. The analysis is based on secondary production data obtained from the Central Statistics Agency (BPS) of Simalungun Regency and North Sumatra Province. LQ analysis is employed to measure the comparative advantage of agricultural commodities by comparing their production concentration at the regency level with that of the provincial level. Commodities with LQ values greater than one are classified as base (leading) commodities, indicating surplus production and export potential. The results show that the horticulture and plantation subsectors exhibit the strongest comparative advantages in Simalungun Regency. Key leading commodities include shallots, cabbage, long beans, large chili, and several vegetables in the horticulture subsector, as well as cocoa, oil palm, Arabica coffee, and Robusta coffee in the plantation subsector. Cocoa records exceptionally high LQ values, indicating a dominant production surplus relative to the provincial average. In contrast, most food crop commodities, except soybeans, and several livestock and fishery commodities remain non-base and primarily serve local demand. Overall, the findings indicate that Simalungun Regency possesses substantial potential to strengthen its regional economy through the development of leading agricultural commodities. Policy efforts should focus on value chain enhancement, infrastructure improvement, institutional strengthening of farmers, and market expansion to support sustainable agricultural-based regional development.